2015
DOI: 10.4314/ahs.v15i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Types and predictors of partner reactions to HIV status disclosure among HIVinfected adult Nigerians in a tertiary hospital in the Niger Delta

Abstract: Background and objective: Our aim was to describe the types and determinants of partner reactions to HIV-status disclosure among adults attending an antiretroviral therapy-(ART) clinic in the Bayelsa State, Nigeria Methods: A cross-sectional study was undertaken between January and March 2013 among consecutive adult patients who had disclosed their HIV-status to their current sexual partner. Sociodemograhic data and types of initial and subsequent partner reactions to disclosure were obtained using interviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…We show HIV post-test counselling to be associated with HIV status disclosure. This conforms with other findings from previous studies by Kadowa and Nuwaha in Uganda [7], Deribe et al in Ethiopia [8], Ogoina et al in Nigeria [9] and Idindili et al in Tanzania [10]. Obermeyer et al reviewed facilitators of HIV status disclosure across diverse settings and their findings suggested that structural changes, including making more services available, could facilitate HIV disclosure as much as individual approaches and counseling do [11].…”
Section: Discussionsupporting
confidence: 88%
“…We show HIV post-test counselling to be associated with HIV status disclosure. This conforms with other findings from previous studies by Kadowa and Nuwaha in Uganda [7], Deribe et al in Ethiopia [8], Ogoina et al in Nigeria [9] and Idindili et al in Tanzania [10]. Obermeyer et al reviewed facilitators of HIV status disclosure across diverse settings and their findings suggested that structural changes, including making more services available, could facilitate HIV disclosure as much as individual approaches and counseling do [11].…”
Section: Discussionsupporting
confidence: 88%
“…We have also identified three studies [34][35][36] which were published after the review was conducted. Following the Cochrane Collaboration guidelines, these are noted as 'awaiting classification' and were included in the review update (see Table 5).…”
Section: Characteristics Of Studies On Hiv Disclosurementioning
confidence: 99%
“…Disclosure to a male partner may occur later or not at all [ 28 , 29 ]. Despite pre-disclosure fears, many women who disclose report surprisingly positive reactions and support from family and male partners [ 6 , 12 , 15 , 17 , 21 , 22 , 30 , 31 ]. Nonetheless, negative consequences have also been reported [ 6 , 12 , 15 , 17 , 18 , 21 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%